Physical, Thermal Stability, and Mechanical Characteristics of New Bioplastic Elastomer from Blends Cassava and Tannia Starches as Green Material - Christwardana, Marcelinus; Ismojo, I.; Marsudi, Sidik (Universitas Jenderal Soedirman, 2021)
This paper presents the study results of the morphology, physical properties, thermal stability, and mechanics of bioplastic blends made from tannia and cassava starch, with a varying weight from 0 to 95%. The addition of tannia to the cassava starch-based bioplastic composition has the ability to reduce the number of pores, density, and water absorption with an average thickness of 0.21-0.29 mm. It also increased moisture content due to its nature, which is more hydrophilic than cassava starch. The result showed that the tensile strength of bioplastic ranged from 0.81-1.33 MPa and elongated from 31-35%. In addition, the thermal analysis data showed that the glass transition temperature shifted marginally due to intermolecular activity. This shows that tannia starch has promising potential as an alternative raw material for bioplastics to replace cassava starch which is more dominantly used as a food source.